Amphiphilic Sialic Acid Derivatives as Potential Dual-Specific Inhibitors of Influenza Hemagglutinin and Neuraminidase - Lőrincz, Eszter Boglárka; Herczeg, Mihály; Houser, Josef; Rievajová, Martina; Kuki, Ákos; Malinovská, Lenka; Naesens, Lieve; Wimmerová, Michaela; Borbás, Anikó; Herczegh, Pál; Bereczki, Ilona (International journal of molecular sciences, 2023)
In the shadow of SARS-CoV-2, influenza seems to be an innocent virus, although new zoonotic influenza viruses evolved by mutations may lead to severe pandemics. According to WHO, there is an urgent need for better antiviral drugs. Blocking viral hemagglutinin with multivalent N-acetylneuraminic acid derivatives is a promising approach to prevent influenza infection. Moreover, dual inhibition of both hemagglutinin and neuraminidase may result in a more powerful effect. Since both viral glycoproteins can bind to neuraminic acid, we have prepared three series of amphiphilic self-assembling 2-thio-neuraminic acid derivatives constituting aggregates in aqueous medium to take advantage of their multivalent effect. One of the series was prepared by the azide-alkyne click reaction, and the other two by the thio-click reaction to yield neuraminic acid derivatives containing lipophilic tails of different sizes and an enzymatically stable thioglycosidic bond. Two of the three bis-octyl derivatives produced proved to be active against influenza viruses, while all three octyl derivatives bound to hemagglutinin and neuraminidase from H1N1 and H3N2 influenza types.
Keywords: neuraminidasa; kyseliny neuraminové; Neuraminidase; sialic acid; Influenza, Human; influenza; Influenza A Virus, H3N2 Subtype; virus chřipky A, podtyp H1N1; hemaglutininové glykoproteiny viru chřipky; Hemagglutinins; Influenza A Virus, H1N1 Subtype; aggregates; kyselina N-acetylneuraminová; Humans; Neuraminic Acids; Hemagglutinin Glycoproteins, Influenza Virus; neuraminidase; virus chřipky A, podtyp H3N2; hemagglutinin; N-Acetylneuraminic Acid; chřipka lidská; hemaglutininy; lidé